South Africa and India's support for the ILO's green initiatives: a comparative study using the postcolonialism lens - Nair, Sharmini, author; Mumme, Stephen, advisor; Lee, Julia, advisor; Lavoie, Anna, committee member; Ciplet, David, committee member (Colorado State University. Libraries, 2022)
The International Labour Organization's (ILO) green initiatives seek to protect vulnerable communities from the impact of climate change on livelihoods. Nevertheless, there has not been universal acceptance of these green initiatives by developing states, which some claim is due to fear of neocolonialism. This research shows that South Africa has been more supportive than India in the formation of green policies within the ILO. This research seeks to explain the following: How do postcolonial theories assist in the analysis of enduring colonial logic in the ILO's environmental policies and South Africa's support of green initiatives at the ILO? Departing from materialist explanations, I utilize postcolonialism, namely Said's Orientalism and Bhabha's mimicry, to explain the responses by South Africa and India towards green policies at the ILO. By doing so, I expand the comparative field using postcolonialism and a heterogenized exploration of responses by labor and states in these two cases. This research is novel through its comparative case study of two major BRICS states and their link to ILO's green policies. Primary research sources will be minutes of ILO proceedings, recorded interviews on the ILO website, digital participant observation, digital fieldwork, and archival analysis. Secondary research sources include historical texts, and biographies of labor/political leaders. Using process tracing and discourse analysis, I produce narratives that depict labor experiences through historical processes, colonial framings, and mimicry. The research project describes how colonialism has shaped relationships between labor, social movements, and government and how it has resulted in disparate responses from South Africa and India at the ILO.
Keywords: India; labor; South Africa; just transition; green jobs; postcolonialism